Impact of techno-economic parameters on the power systems model with high share of renewable energy and energy storage - Sarhan A. (John Wiley and Sons Ltd, 2023)
Cost benefit analysis; Cost effectiveness; Costs; Decision making; Economic analysis; Economic and social effects; Renewable energy resources; Design and operations; Optimal generation; Power systems modeling; Renewable energies; Renewable generation; Spatial temporals; Systematic analysis; Techno-economics; Energy storage